Kompetensi Pedagogik Guru dalam Melaksanakan Penilian Pembelajaran Anak Usia Dini di KB Teratai Lanal - Renawati Renawati; Amelia Amelia; Mila Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the pedagogical competence of teachers in conducting assessments of early childhood at KB Teratai. Pedagogical competence refers to the teacher’s ability to manage children's learning, including planning, implementing, and evaluating assessments of student development. Assessment in early childhood requires a deep understanding of children’s developmental characteristics as well as the use of appropriate assessment methods such as observation, documentation, and portfolios. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that teachers at KB Teratai possess a basic understanding of the principles and techniques of developmental assessment; however, several obstacles remain in its implementation, such as limited time, supporting facilities, and the need for further training. These findings highlight the importance of continuous improvement of teachers’ pedagogical competence to support the quality of early childhood development assessments. Based on the results of this study, pedagogical competence is essential for teachers and can be observed through their ability to use educational play tools as a medium in the learning process.